[Nowy Port, kanał portowy] [Aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia kanał portowy w Nowym Porcie, zacumowane przy nabrzeżach statki, ok. 1910 r.